Inter-brain synchrony between undergraduate students during a naturalistic online seminar predicted greater relational satisfaction and task performance - Azhari, Atiqah; Rai, Ashvina; Ho, Han Sheng; Jegathisan, Ajevan; Gill, Shafeeqah; Norfor, Noelle; Chen, Zan (Frontiers in Neuroscience, 2025)
As higher education increasingly transitions to online platforms such as Zoom, understanding the mechanisms that underlie effective virtual collaboration has become essential. Prior research has shown that relational quality, trust, and communication strongly influence online collaborative learning; however, the real-time cognitive and affective dynamics underpinning these interactions are yet to be elucidated. This study addresses this gap by examining inter-brain synchrony (IBS)—the alignment of neural activity between individuals—as an indicator of collaborative success. Using functional Near-Infrared Spectroscopy (fNIRS) hyperscanning, we investigated IBS in 30 dyads of undergraduate students engaged in a naturalistic three-phase Zoom seminar comprising lecture viewing, interactive discussion, and a presentation. Inter-brain synchrony between partners was computed in the prefrontal cortex, and outcomes were assessed via relational satisfaction questionnaires and standardized ratings of presentations. Results showed that IBS emerged predominantly during active discussions, but not during passive lecture viewing, underscoring the importance of interactive engagement in generating neural alignment. Crucially, higher IBS during discussion predicted both greater group relational satisfaction and improved task performance. These findings extend prior evidence that IBS supports cooperation, demonstrating that neural synchrony can occur even without physical co-presence and is associated with both performance and satisfaction in virtual educational settings.